Public health foundations : concepts and practices - Andresen, Elena; Bouldin, Erin DeFries (San Francisco, CA : Jossey-Bass, 2010)
"Foundations of Public Health is a concise yet comprehensive text that offers an excellent and engaging introduction to the field of public health. This important resource is an up-to-date introduction to the core concepts and the practices of public health. The book introduces public health in concept and its systems; the foundational tools of data, epidemiology, biostatistics, and key study designs; populations' issues including infectious disease, health behavior, and environmental health plus analytical tools of qualitative research and risk assessment; and how health services are formulated and delivered."--
Includes bibliographical references and index.
Keywords: Public health -- United States; Epidemiologic Methods -- United States; Health Behavior -- United States; Health Policy -- United States